Respon Perkecambahan Benih Jagung (Zea mays. L) Pada Kondisi Cekaman Garam: Respon Perkecambahan Benih Jagung (Zea mays. L) Pada Kondisi Cekaman Garam - Kalis Amartani (Universitas Bangka Belitung, 2019)
Germination is first stepping propagation a plant especially of plants yielding seed. Salinity effect during the germination phase can cause obstructed of seed grain because seed grain to experience plasmolysis. The aim of the research to know germination response seed grain of corn in the condition of a stress salt. This experimental was arranged in randomized complete design (RCD) with five replication. This research was done by germinated seed grain of corn in the seedling medium contained salt with the kind of concentration were 0 ppm (control), 2000 ppm, 4000 ppm, 6000 ppm, 8000 ppm then observation of germination seed process 14 days after seedling. The average value was counted with the F test and continued Honestly significant different at the 0,05 significant level. The result showed variable stress salt with concentration 4000 ppm not different significant with concentration 0 ppm